An Analysis of Students’ Ability In Paraphrasing A Paragraph at The English Department Universitas Negeri Padang - Gito Rusdianto; Fitrawati Fitrawati (Universitas Negeri Padang, 2022)
This article deals with students’ ability in paraphrasinga paragraphat The English Department Universitas NegeriPadang.This descriptive quantitative research aimed to analyze students' ability in paraphrasing a paragraph text based on Leonhard's paraphrasing rubric (2002) and to identify problems in students' paraphrasing based on the theory of Kennedy & Smith (1986). The sample of this research was 27 (twenty-seven) students of the K4 class at the English Language Education Study Program, Universitas Negeri Padang, for the 2020 academic year. The data was collected using a paraphrasing test as the instrument in which they paraphrased a paragraph of text. The finding showed that the average score in the paraphrasing test was 51,9, categorized as unsatisfactory. The researcher also concluded the number of problems in students' paraphrasing a paragraph was 55. In general, 40% of students' paraphrases were classified as substituting inappropriate synonyms. 29% of students' paraphrases were classified as leaving out important information. 20% of students' paraphrases were classified as including too much of the original, 11% of students' paraphrases were classified as misreading the original, and there was no problem of adding opinion summarizing rather than paraphrasing found in students' paraphrases. Studying these two topics is very useful for understanding how students' ability to paraphrase a paragraph can be optimally increased.